Enterprise Arsitektur Planning (EAP) untuk Universitas Pattimura menggunakan TOGAF ADM - Roberth Everthardus Pariama; Andi W. R. Emanuel (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
AbstractThe application of Enterprise Architecture (EA) is an important concept required by large-scale tertiary institutions. Application of EA that helps. The importance of EA starts from structuring SI strategies that support lectures, Information Technology (IT) services, data, applications and future technology. The Strategic Plan and Master Plan for Pattimura University Development become a reference in the implementation of EAP, and also interviews for students, lecturers and employees of IT management become the author's research method, thus finding concrete data to be used by Pattimura University EA. TOGAF ADM is work or framework that supports the company's architecture and is also a method of developing a company's architecture used by researchers. Blueprints of business architecture, data, information systems applications and technology are the results of EA modelling that is applied to the Pattimura University distribution room. TOGAF ADM in the Preliminary Phase or the initial phase of a corporation, data, application and technology. In the Architecture Vision phase, it produces an architectural vision between business architecture, data, applications and other technologies. In the Business Architecture phase, it produces a business architecture blueprint. In the Information Systems Architecture phase, it produces a blueprint for the SI architecture, and in the Technology Architecture phase, it produces a blueprint for the IT architecture. The application of the EAP method at Pattimura University has a positive impact because it produces an alignment of business strategies and IT strategies is very important to be applied.